Low-density lipoprotein subclass patterns and risk of myocardial infarction - Austin, M A; Breslow, J L; Hennekens, C H; Buring, J E; Willett, W C; Krauss, R M (JAMA : the journal of the American Medical Association, 1988)
The association of low-density lipoprotein (LDL) subclass patterns with coronary heart disease was investigated in a case-control study of nonfatal myocardial infarction. Subclasses of LDL were analyzed by gradient gel electrophoresis of plasma samples from 109 cases and 121 controls. The LDL subclass pattern characterized by a preponderance of small, dense LDL particles was significantly associated with a threefold increased risk of myocardial infarction, independent of age, sex, and relative weight. Plasma levels of high-density lipoprotein cholesterol were decreased, and levels of triglyceride, very low-density lipoproteins, and intermediate-density lipoproteins were increased in subjects with this LDL subclass pattern. Multivariate logistic regression analyses showed that both high-density lipoprotein cholesterol and triglyceride levels contributed to the risk associated with the small, dense LDL subclass pattern. Thus, the metabolic trait responsible for this LDL subclass pattern results in a set of interrelated lipoprotein changes that lead to increased risk of coronary heart disease.